Planned fiscal consolidations and growth forecast errors: New panel evidence on fiscal multipliers - Ansgar Belke; Dominik Kronen; Thomas Osowski (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
This paper analyzes the effect of planned fiscal consolidation on GDP growth forecast errors from the years 2010-2013 using cross section analyses and fixed effects estimations. Our main findings are that fiscal multipliers have been underestimated in most instances for the year 2011 while we find little to no evidence for the years 2010 and especially the latter years 2012/13. Since the underestimation of fiscal multipliers seems to have decreased over time, it may indicate learning effects of forecasters. However, the implications for fiscal policy should be considered with caution as a false forecast of fiscal multipliers does not confirm that austerity is the wrong fiscal approach but only suggests a too optimistic assessment of fiscal multipliers for the year 2011. – – Diese Arbeit analysiert den Effekt geplanter fiskalischer Konsolidierungen auf den Prognosefehler des BIP-Wachstums für die Jahre 2010-2013 mittels Querschnittsanalysen und Fixed Effects Modellen. Unsere Ergebnisse zeigen, dass fiskalische Multiplikatoren im Jahr 2011 in den meisten Fällen unterschätzt wurden, während für das Jahr 2010 und speziell die späteren Jahre 2012 und 2013 wenig bis gar kein Anzeichen einer Unterschätzung zu finden ist. Die Unterschätzung fiskalischer Multiplikatoren nimmt mit der Zeit ab, was ein Zeichen für Lerneffekte bei der Prognose sein könnte. Die Implikationen für die Fiskalpolitik sollte allerdings vorsichtig betrachtet werden, da ein falscher fiskalischer Multiplikator nicht impliziert, dass Austerität das falsche haushaltspolitische Vorgehen ist. Es ist lediglich eine zu positive Einschätzung fiskalischer Multiplikatoren für das Jahr 2011 festzustellen.
Keywords: C23; E61; E62; G01; 330; fiscal multiplier; austerity; growth forecast errors; panel econometrics